Chapter The Unattainable South African Paradise - Virga, Anita (Studi e saggi, 2021)
Whether Dante was part of a hegemonic discourse or a counter one, he helped to shape identities, create new ones, re-imagined old ones. However, for these young South African students whose contributions are collected in this book Paradise as a place of the future seems to remain an unattainable mirage. For them South Africa is locked in a present which cannot overcome its past and cannot imagine its future; an eternal Purgatory, which ironically enough for Dante is the only non-eternal place of the afterlife.